2006
DOI: 10.1177/107906320601800107
|View full text |Cite
|
Sign up to set email alerts
|

Sex Offenders' Response to Treatment and its Association with Recidivism as a Function of Psychopathy

Abstract: This study examined the relationship between recidivism and ratings of response to specialized cognitive behavioral treatment conducted in a prison setting among 418 sex offenders released to the community for an average follow-up period of over 5 years. As well as testing for a main effect for treatment ratings, the potential role of psychopathy assessed using the Psychopathy Checklist--Revised (PCL-R) as a moderator of response to treatment was investigated. Ratings of response to treatment failed to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 38 publications
1
30
0
5
Order By: Relevance
“…The exception was the d = 0.96 effect from a study (Beggs & Grace, 2008) in which offenders were scored on the PCL-R at the end of a 9-month intensive treatment program by therapists who knew the offenders well (S. Beggs, personal communication, December 23, 2011). This scenario appears unusual compared to other field studies, in which scores appear to have been assigned by clinicians conducting intake assessment at the start of treatment or incarceration (e.g., Langton et al, 2006) or by practicing forensic evaluators (e.g., Murrie et al, 2012). In both of the latter scenarios, clinicians may still have ample access to law enforcement records but may have less opportunity to observe and interact with offenders over extended time.…”
Section: Fieid Versus Research Scoresmentioning
confidence: 91%
“…The exception was the d = 0.96 effect from a study (Beggs & Grace, 2008) in which offenders were scored on the PCL-R at the end of a 9-month intensive treatment program by therapists who knew the offenders well (S. Beggs, personal communication, December 23, 2011). This scenario appears unusual compared to other field studies, in which scores appear to have been assigned by clinicians conducting intake assessment at the start of treatment or incarceration (e.g., Langton et al, 2006) or by practicing forensic evaluators (e.g., Murrie et al, 2012). In both of the latter scenarios, clinicians may still have ample access to law enforcement records but may have less opportunity to observe and interact with offenders over extended time.…”
Section: Fieid Versus Research Scoresmentioning
confidence: 91%
“…There is some evidence that psychopathic sex offenders are able to manipulate skilled therapists into wrongly concluding that they have made treatment gains, causing therapist progress ratings to be unrelated to recidivism (Looman et al, 2005;Seto & Barbaree, 1999). However, recent evidence supports the conclusion that treatment may effectively reduce recidivism for some psychopaths and that therapist's ratings are indeed related to reoffending (Barbaree, 2005;Langton et al, 2006). Most clearly, when an adequate amount of intensive treatment is provided for youth with psychopathic traits, rates of violent recidivism are reduced (Caldwell, Skeem, Salekin, & Van Rybroek, 2006).…”
Section: Disproportionate Influence Of Modest Research Findings On Exmentioning
confidence: 99%
“…PCL-R scores predict general offending and violent offending (Lesticio, Salekin, DeCoster, & Rogers, 2008) to such a degree that some have argued it would be irresponsible for forensic decision makers to fail to take psychopathy into consideration (Heilbrun, Ogloff, & Picarello, 1999). 1 Psychopathic traits predict serious reoffending but are also associated with lower receptivity to currently available treatment programmes (Langton, Barbaree, Harkins, & Peacock, 2006;Looman, Abracen, Serin, & Marquis, 2005;Ogloff, Wong, & Greenwood, 1990). As a result, decision makers may also adopt the PCL-R as a proxy measure of treatment amenability.…”
mentioning
confidence: 99%
“…In relation to sexual offenders, psychopathy has been shown to be particularly inimical to positive treatment outcomes. It has been shown to relate to higher rates of treatment dropout and faster sexual and violent recidivism (Barbaree, 2005;Gretton et al, 2001;Hildebrand et al, 2004;Langton et al, 2006;Looman et al, 2005;Olver & Wong, 2006, 2009. Most worryingly, those psychopathic individuals who appeared to be doing better in treatment were in one study found to be more likely to recidivate than those who were rated as having poorer treatment behaviour (Seto & Barbaree, 1999).…”
mentioning
confidence: 99%